TINJAUAN YURIDIS TERHADAP PENYELESAIAN TINDAK PIDANA KEKERASAN SEKSUAL YANG DILAKUKAN OLEH ANAK DI BAWAH USIA 12 TAHUN - Hasdania, Nabila Triyuliani; R, Mukhlis; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Sexual violence is not only carried out by adults, but also by minors. LawNumber 11 of 2012 concerning the Juvenile Criminal Justice System limits theage of children in conflict with the law to 12 years old. Therefore, perpetratorswho are not yet 12 years old cannot be processed formally or in other wordscannot be punished. The rise of sexual crimes committed by children under theage of 12 certainly creates contradictions in society, considering that the crimescommitted cause serious losses to the victims but the perpetrators cannot beprosecuted because they are still minors. The aim of this research is first toexplain the regulation and enforcement of the law when criminal acts of sexualviolence are committed by children under the age of 12 years.The type of research used is normative legal research using librarymaterials as data and reference sources. This research requires secondary dataconsisting of primary, secondary and tertiary legal materials. The data collectiontechnique used by researchers is literature study. In drawing conclusions,researchers use a deductive method, namely drawing conclusions from generalstatements or propositions to specific statements or propositions.From the results of discussions and research carried out, regulation andlaw enforcement for children under 12 years old is still not in line with societaldevelopments. Law Number 11 of 2012 concerning the Juvenile Criminal JusticeSystem still does not fulfill a sense of justice for the victims because the handlingof the perpetrators is not commensurate with the losses experienced by thevictims.Keyword: Sexual Violance, Minors, Sanction